A new species of rust fungus on the New Zealand endemic plant, Myosotidium, from the isolated Chatham Islands - Padamsee, Mahajabeen; Mckenzie, Eric H.c. (Phytotaxa, 2014)
Pucciniastrum myosotidii sp. nov. is described from plants of the Chatham Island forget-me-not (Myosotidium hortensium), a host plant that has a conservation status of “nationally endangered”. The rust has been found only on cultivated plants and not on wild plants. Although no teliospores were found, LSU and SSU sequence analysis showed that the new rust is closely related to some species of Pucciniastrum and Thekopsora forming a weakly supported clade together with P. boehmeriae, P. epilobii, P. circaeae, P. goeppertianum, P. guttatum, P. pustulatum, T. minima and Melampsorella symphyti. If this rust is endemic to Chatham Islands, then it must be accepted as a species of conservation value since the host plant is under threat from grazing animals and habitat loss.